Impact of different pretreatments and attachment materials on shear bond strength of indirectly bonded brackets using CAD/CAM transfer trays to monolithic zirconia. Issue 2 (February 2023) - Jungbauer, Rebecca; Hammer, Christian M.; Edelhoff, Daniel; Proff, Peter; Stawarczyk, Bogna
Abstract: Objective: Investigating the impact of different pretreatment methods, attachment materials and aging regimens on shear bond strength (SBS) between zirconia and indirectly bonded brackets using CAD/CAM transfer trays. Methods: Zirconia substrates were conditioned with silica coated alumina (CoJet) and a) Clearfil Ceramic Primer Plus (CF), b) RelyX Ceramic Primer (RXP), c) Futurabond U (FU). Brackets were virtually placed, transfer tray designed (OnyxCeph) and 3D-printed for indirect bonding with a) Transbond LV (TBL), b) Nexus NX3 (NX3), c) Maximum Cure (MC). SBS testing was performed with a universal testing machine after 24 h, 500 thermal cycles, 90 d. Directly bonded brackets to human enamel using Transbond XT Adhesive served as control. The adhesive remnant index (ARI) was evaluated. Data was analyzed with Shapiro–Wilk, Kruskal–Wallis and Dunn's post-hoc test with Bonferroni correction, Chi 2 test (p < 0.05), and the Weibull modulus was calculated. Results: SBS ranged from 0.1 to 15.5 MPa and were influenced mostly by the attachment material. NX3 generally showed the highest values (9.5–15.8 MPa). Initially RXP/TBL and FU/TBL presented the lowest values (4.3/4.8 MPa). Aging regimens reduced SBS of MC irrespective of pretreatment, after 90 d values ranged from 0.1 to 0.9 MPa. ARI 1 was predominant in all MC groups and FU/NX3, 2 and 3 in the other groups. Weibull moduli ranged between 0.15 (MC/RXP/500 TC) and 6.24 (NX3/RXP/500 TC). Significance: MC seems not to be suitable for indirect bonding using CAD/CAM transfer trays to zirconia. NX3 showed similar SBS values compared to the control, TBL lower. Highlights: Shear bond strength of different attachment materials combined with different pretreatments and aging regimens was measured. Nexus NX3 irrespective of the pretreatment showed sufficiently high shear bond strength values. Transbond LV supreme showed lower values compared to the control. Maximum Cure did not reach clinical acceptable shear bond strength values.